Shear behaviour of high strength concrete walls subjected to cyclic lateral loading - Chandra, Jimmy (2017)
This experimental study investigated shear behaviour of high strength concrete (HSC) walls with concrete strength about 100 MPa. Parameters investigated are wall height to length ratio, vertical and horizontal web reinforcement ratios, and presence of boundary elements. The experimental results show that the shear strength of RC walls is greatly affected by wall height to length ratio. Furthermore, both vertical and horizontal web reinforcement have contribution to the shear strength of RC walls and their effectiveness depends on wall height to length ratio. In addition, presence of boundary elements can increase significantly the shear strength of RC walls. Analytical models have been developed based on truss analogy to predict shear strengths of RC walls. Data from past experiments on RC walls and from this study are used to verify the accuracy of the proposed models. Furthermore, building codes and other analytical model predictions are included as well for comparison. The analysis results show that the proposed models are more accurate than building codes and other analytical models. They have lower coefficient of variation values as compared to other predictions. In addition, the proposed models can predict the shear strength of RC walls with consistent accuracy for wide ranges of wall height to length ratios and concrete strengths which is not the case for building codes and other analytical model predictions.